Review of Evidence‐Based Methods for Successful Labor Induction. (13th May 2021) - Carlson, Nicole; Ellis, Jessica; Page, Katie; Dunn Amore, Alexis; Phillippi, Julia
Abstract: Induction of labor is increasingly a common component of the intrapartum care. Knowledge of the current evidence on methods of labor induction is an essential component of shared decision‐making to determine which induction method meets an individual's health needs and personal preferences. This article provides a review of the current research evidence on labor induction methods, including cervical ripening techniques, and contraction stimulation techniques. Current evidence about expected duration of labor following induction, use of the Bishop score to guide induction, and guidance on the use of combination methods for labor induction are reviewed.